Assessing Validity of Some Critiques towards the Fatwas of the DSN - MUI on Mudarabah within the Perspective of the Aqwal of Islamic Legal Expert - Kamaluddin, Safrudin Halimy; Sudarman, Sudarman (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2020)
Abdullah Saeed and Mervyn K. Lewis argue that the implementation of contracts in Islamic banking has deviated from fiqh. With the same critical framework, some researchers in Indonesia also criticize the fatwas of the DSN-MUI (National Sharia Board of the Indonesian Ulema Council) on the muḍārabah contract. This paper, however, argues that all of those criticisms can be categorized as a khilāfiyyah (differences of opinion among muslim jurists). Again this backdrop, this paper will assess the validity of those critiques towards the fatwas of the DSN-MUI on muḍārabah within the perspective of the aqwāl of islamic legal experts (madhāhib) as well as prove that the muḍārabah model in Islamic banking in Indonesia does not deviate from fiqh. After reviewing relevant library sources, this paper shows that the fatwas of the DSN-MUI on muḍārabah are supported by the aqwāl of islamic legal experts among Ḥanbalī, Ḥanafī, Mālikī, and Shāfiʻī schools. Moreever, although it is different from the muḍārabah form known by many people in fiqh, the muḍārabah contract system adopted by the DSN-MUI can be categorized as a model of muḍārabah permitted by islamic legal experts.